Water-Repellent Approaches for 3-D Printed Internal Passages. Issue 9 (3rd July 2016) - Milionis, A.; Noyes, C.; Loth, E.; Bayer, I. S.; Lichtenberger, A. W.; Stathopoulos, V. N.; Vourdas, N.
Abstract : In this work, two different manufacturing approaches are presented that create water-repellency (hydrophobicity and super-hydrophobicity) for acrylonitrile butadiene styrene (ABS) structures. In particular, this is the first study to render three-dimensional (3-D) printed ABS surfaces with internal flow paths to be superhydrophobic. The first approach uses standard wet-based chemical processing for surface preparation after which a fluorocarbon layer is deposited by dip coating or with vapor deposition. This first approach creates hydrophobic surfaces with roll-off angles of less than 30°. In the second approach, the ABS structures are dip-coated with a commercial rubber coating solution and subsequently surface-modified by reactive ion etching (RIE) with fluorinated gases to render the samples superhydrophobic, with roll-off angles as low as 6°. In order to further enhance their water-repellency, the dip-coating rubber solution is mixed with polytetrafluoroethylene (PTFE) colloidal dispersions to form a nanocomposite layer prior to the RIE process. The PTFE particles induce surface roughness as well as hydrophobicity. The modified surfaces created by the two approaches are further characterized by scanning electron microscopy and water drainage performance. Water drainage (prevention of water retention) is especially important for high thermal efficiency of 3-D printed heat exchangers. However, water-repellency for ABS is also interesting for a broader range of applications that use this material.